2021
DOI: 10.1590/1983-1447.2021.20190361
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted debriefing technique for nursing simulation: how to proceed?

Abstract: Objective: To identify elements in scientific literature that make the video-assisted debriefing technique feasible in the teaching and learning process, in nursing simulation. Method: Integrative literature review, conducted from May to July of 2019. Primary studies, with no time frame, were selected in Portuguese, English or Spanish, in the PubMed®, Scopus®, CINAHL and LILACS databases, using the Rayyan application. Qualitative analysis was adopted. Results: 205 studies were initially identified, six of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Because simulation-supported nursing education addresses multiple sensory organs, it provides more information transfer, skill learning becomes more understandable, and students' problem-solving skills increase. 6,[34][35][36]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because simulation-supported nursing education addresses multiple sensory organs, it provides more information transfer, skill learning becomes more understandable, and students' problem-solving skills increase. 6,[34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tran et al, 33 students stated that they saw the applications more clearly while watching the virtual patient videos created and that th7s improved their learning process. Because simulation-supported nursing education addresses multiple sensory organs, it provides more information transfer, skill learning becomes more understandable, and students' problem-solving skills increase 6,34–36 …”
Section: Discussionmentioning
confidence: 99%
“…However, we restricted them to oral debriefing sessions and believed it to be more amenable. 15 In a randomized controlled trial comparing oral debriefing and video-assisted debriefing sessions in teaching neonatal resuscitation protocols, the authors found that debriefing sessions for 15 minutes had potential benefits in improving neonatal resuscitation skills. However, there was no difference between oral and video-assisted debriefing sessions.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted debriefing sessions for 1 hour to make it more amenable to participants. Participants with pretest and posttest DOPS scores were segregated into the following categories: below expectation (0-4), borderline expectations (5)(6)(7)(8), meeting expectations (9)(10)(11)(12), and above expectations (13)(14)(15)(16), and it was found that scores were significantly improved after being exposed to the teaching module, with a P value <.001. When participants were segregated with DOPS scores >12 versus those with DOPS scores lower than or equal to 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation